2012
DOI: 10.1111/j.1755-3768.2012.f004.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IOP and biomechanical corneal values obtained by ORA

Abstract: Purpose To evaluate the relationship between intraocular pressure (IOP) measurements and corneal biomechanical parameters obtained with Ocular Response Analyser (ORA) in healthy subjects. Methods Sixty‐five eyes from 65 healthy subjects were prospective and consecutively selected. All of them underwent a full optometric examination, including central corneal thickness (CCT) and IOP measured with ORA: ORA Goldmann‐corrected IOP (IOPg) and ORA corneal resistance‐corrected IOP (IOPcc). Pearson correlation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In this study, we observed that CH increased with the decrease of IOPcc in the pregnant subjects, which also supported a negative correlation between IOPcc and CH ( r = −0.482) from a previous report. 26 A positive correlation between CCT and CH found in our study has also been consistently described in previous publications. 24,27 Nevertheless, we found that CH in the second and the third trimester is significantly higher than that of non-pregnant group after adjustment for IOPcc, indicating the changes in CH in the advancing stages of pregnancy are independent of IOPcc.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observed that CH increased with the decrease of IOPcc in the pregnant subjects, which also supported a negative correlation between IOPcc and CH ( r = −0.482) from a previous report. 26 A positive correlation between CCT and CH found in our study has also been consistently described in previous publications. 24,27 Nevertheless, we found that CH in the second and the third trimester is significantly higher than that of non-pregnant group after adjustment for IOPcc, indicating the changes in CH in the advancing stages of pregnancy are independent of IOPcc.…”
Section: Discussionsupporting
confidence: 92%
“…Correlation of these parameters relative to biometric measurement and IOP remains the subject of studies. According to Lopez de la Fuente et al [20], there is an average negative correlation between IOPcc and CH measured in the patient (r = -0.482). That conclusion was confirmed by studies [9,10], where higher CH values were obtained for lower IOPcc measurements.…”
Section: Biomechanical Parameters Of the Cornea: Ch And Crfmentioning
confidence: 93%